Plasmon‐Polariton Induced, "from Surface" RAFT Polymerization, as a Way toward Creation of Grafted Polymer Films with Thickness Precisely Controlled by Self‐Limiting Mechanism. Issue 22 (4th October 2018) - Erzina, Mariia; Guselnikova, Olga; Postnikov, Pavel; Elashnikov, Roman; Kolska, Zdenka; Miliutina, Elena; Švorčík, Václav; Lyutakov, Oleksiy
Abstract: Plasmon‐induced "from surface" reversible addition‐fragmentation chain‐transfer (RAFT) polymerization is reported for the first time. The gold grating surface, supporting the surface plasmon polariton excitation and propagation, is grafted with RAFT agent, immersed in the solution, containing the NIPAm monomer and AIBN and subsequently illuminated at a wavelength corresponding to plasmon absorption. The grafting of the polymer layer, its thickness, and morphology are characterized by several techniques (including the surface‐enhanced Raman spectroscopy (SERS), scanning electron microscopy and energy‐dispersive X‐ray spectroscopy (SEM‐EDX), X‐ray photoelectron spectroscopy (XPS), nanomechanical atomic force microscopy (AFM) mapping, and goniometry). It is shown that the polymerization efficiently starts only under the surface plasmon‐polariton excitation. The time‐dependent SERS and XPS measurements indicate rather self‐limiting nature of plasmon‐induced "from the surface" PNIPAm growth, namely the reaction takes place up to a certain polymer thickness and is stopped despite a significant excess of polymerization initiator and monomer in the reaction solution. The present results provide the basis for designing further experiments on plasmonic catalysis in general and offer a new way of producing ultrathin polymer films with a defined structural dimension. Abstract : Plasmon‐induced "from surface" reversible addition‐fragmentation chain‐transfer (RAFT) polymerization is reported for the first time. Coupling of light energy into plasmonic modes leads to efficient activation of initiator in the proximity of RAFT‐grafted plasmonic surface and to subsequent surface assisted growth of poly( N ‐isopropylacrylamide) chains. The polymerization takes place up to a certain polymer thickness and is then self‐stopped.